PENGARUH VOLATILITAS NILAI TUKAR RUPIAH TERHADAP NILAI TUKAR RUPIAH : APLIKASI MODEL ARCH/GARCH - Theressia Mellyastannia; Syafri Syafri (Lembaga Penerbit Fakultas EKonomi dan Bisnis, 2022)
The purpose of this study was to determine the effect of volatility in the rupiah /U.S. against the rupiah / U.S. . Analysis model used in this study is a model of ARCH /GARCH. Control variables are included in the data processing is a variable rate 12-month deposit rate and the current account. The period of data used are monthly data from years 2001 to 2012. From the results of the model estimates the chosen ARCH 2 as the best model to estimate the volatility of the exchange rate. The estimation results indicate that exchange rate volatility and a significant positive effect on the exchange rate. Meanwhile, the interest rate on 12-month deposits and current account negatively affect the exchange rate significantly.